Effect of Sowing Dates and Varities on Yield and Yield Attributes of Direct Seeded Rice in Chitwan Condition - Dawadi, KP; Chaudhary, NK (Journal of Agriculture and Environment, 2013)
Rice transplanting and sowing time sometimes get delayed due to lack of assured irrigation or surplus of rainfall. Moreover, no specific varieties have been specifically developed for this purpose. An experiment was conducted to study the effect of sowing dates and varieties on growth and yield of direct seeded rice during rainy season in 2010. The experiment was laid out in split plot design with four sowing dates and three varieties in sub plot. Sowing date on June 13th contributed to higher grain yield; higher gross return; net return and higher B:C ratio per hectare. Similarly, the variety Hardinath-1 excelled better in all these parameters with early maturity. The interaction effect of Hardinath-1 with June 13 sowing took lower days for maturity; produced higher number of effective tillers (386.3); heat use efficiency (2.14); straw yield (7.43 t ha-1); and relatively higher grain yield (4.22 t ha-1); gross return (Rs.108.55 thousand); net return (Rs. 51.22 thousands) and B:C ratio (1.89). Therefore, variety Hardinath-1 with June 13 sowing is best suited to get higher yield, timely maturity and higher economic return in Chitwan conditions.